Escore de cálcio e redução luminal associado a funcionalidade e capacidade física em pacientes com doença arterial coronária - Matos, Carlos José Oliveira de (2017)
INTRODUCTION: The coronary computed tomography angiography (CTA) with evaluation of coronary artery calcium score (CACS) and coronary stenosis by reducing luminal is a method that enables evaluation of cardiovascular risk in patients with subclinical atherosclerosis. The diagnosis of coronary artery disease (CAD) may contribute to the perception of possible impact on daily activities that affect the autonomy of the person. OBJECTIVE: To evaluate the functionality and physical ability and your association with CACS and coronary stenosis in patients with CAD. METHODOLOGY: Cross-sectional study with 208 consecutive patients, both genders, in two hospitals that perform CTA in Aracaju/Brazil. Patients underwent the assessment functional through the functional independence measure (FIM), Katz index modified, Barthel index and the 6-minute walk test. Then, patients underwent CTA for quantification of CACS and the degree of coronary stenosis and the number of vessels affected. We used the chi-square test, ANOVA and Tukey for analysis between intra-group, and linear regression to assess association between variables. A significance level of 5% using the SPSS 21.0. RESULTS: The mean age was 57.0±11.2 years, with 61.5% female. The most frequent risk factors were high blood pressure (78.4%), followed by family history (72.1%). 9.9% of the sample had previous CAD. The most frequent symptoms was typical precordialgia (39%). The CACS was changed in 49.5% of the patients, being the group of CACS intermediate (23.8%). The FIM presented 81% of the maximum value, and the distance traveled of 67.9% of the predicted distance, and difference was observed between the distance travelled between the CACS groups (p = 0.03). The functional dependence showed dependence of with the sedentary lifestyle (p=0.007), and dyspnea (p=0.008), while the physical capacity independently influence presented with dyspnea (p=0.03). CONCLUSION: Reduction in physical capacity was associated with a higher increase in the CACS and greater luminal reduction in patients with CAD, and functionality reduced in the higher CACS groups, presenting sedentary lifestyle and dyspnea as independent associated factors, which suggests a greater impact functional in these patients.